An Analysis of Grammatical Cohesion in Exposition Text Written by Eleventh Grade Students in MAN 2 Padang - Ilham Al Khairi; Wahyuni Delvi (Universitas Negeri Padang, 2020)
This study aimed to analyse the use of grammatical cohesive devices in an analytical exposition text written by eleventh grade students of MAN 2 Padang based on Halliday and Hasan’s theory (1976). Grammatical cohesive devices was used in order to write a cohesive text for helping both writer and reader. The participants of this research were 65 eleventh grade students in MAN 2 Padang. This study was descriptive qualitative research used in analysing the grammatical cohesive devices in an analytical exposition text. The instrumentations of this research were There were some instrumentations used in this research such as: writing test, table analysis and formulation. The findings of the research showed that all of the grammatical cohesive devices; reference, substitution, ellipsis and conjunction; used by the students in writing a text. There were 1.225 grammatical cohesive used by the students in writing an analytical exposition text. However, ellipsis and substitution were rarely used in that text.